Crisis de violencia social y su impacto en la salud mental del personal de enfermería del Hospital General Martín Icaza. Noviembre 2023 – abril 2024. - Sánchez Valverde, Melissa Katherine (2024)
The continued insecurity in Ecuador can have serious consequences in all areas of life. Terrorism causes fear and violence, with prolonged psychological consequences. Affected communities and health personnel experience high levels of stress, anxiety, and depression due to the constant feeling of vulnerability. There is no current research on the impact of the social violence crisis in Ecuador on health personnel, including nursing personnel. Experts in psychology and psychiatry explain that anxiety is a common reaction to violence, perceived as nervousness due to the uncertainty generated by insecurity. Next comes hypervigilance and mood changes, such as irritability or depression, due to stress. Therefore, the aim of the research is to analyze the crisis of social violence and its impact on the mental health of the nursing staff at the Martin Icaza Hospital during the period November 2023 - April 2024. The methodology used was quantitative, descriptive, and documentary, the sample used in the research is 85 members of the nursing staff who work at the Martin Icaza Hospital during the period November 2023 - April 2024.